2022
DOI: 10.3390/ijms231810388
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body Vibration Improves Brain and Musculoskeletal Health by Modulating the Expression of Tissue-Specific Markers: FNDC5 as a Key Regulator of Vibration Adaptations

Abstract: Whole body vibration (WBV) is well known to exert beneficial effects on multiple tissues, improving synaptic transmission, muscle mass, bone quality, and reducing anxiety and depressive behavior. However, the underlying molecular mechanisms are not yet fully understood, and organs and tissues may respond differently to the vibratory stimulus depending on multiple factors. Therefore, we investigated the WBV effects on the brain and musculoskeletal tissue of 4-month-old young mice, evaluating synaptic plasticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In contrast, the other vibration training protocols, which differed in vibration frequency, vibration exposure time and recovery time, were found to be too stressful, inducing the appearance of an epileptic tendency and possibly damaging the hippocampus and other brain structures related to memory functions [ 31 ]. These results were later confirmed by the same authors through histological and morphometric analyses, showing that reduced synaptic function was associated with the presence of structural alterations, including a reduction in the number of Purkinje cells in the cerebellum, as well as reduced or even absent pyramidal neurons in the hippocampus, indicating WBV-induced sensory stimulation as an essential part of the mechanism underlying the improved cognitive performance in mice [ 32 ].…”
Section: Physiological Adaptations To Wbvmentioning
confidence: 71%
See 3 more Smart Citations
“…In contrast, the other vibration training protocols, which differed in vibration frequency, vibration exposure time and recovery time, were found to be too stressful, inducing the appearance of an epileptic tendency and possibly damaging the hippocampus and other brain structures related to memory functions [ 31 ]. These results were later confirmed by the same authors through histological and morphometric analyses, showing that reduced synaptic function was associated with the presence of structural alterations, including a reduction in the number of Purkinje cells in the cerebellum, as well as reduced or even absent pyramidal neurons in the hippocampus, indicating WBV-induced sensory stimulation as an essential part of the mechanism underlying the improved cognitive performance in mice [ 32 ].…”
Section: Physiological Adaptations To Wbvmentioning
confidence: 71%
“…Similarly, Shan and colleagues showed that knockout of the myostatin gene produces an increase in the muscle mass and browning of adipose tissue, effects known to be attributed to irisin [ 86 ]. In agreement with this, Cariati et al recently studied the potential effects of WBV on the expression of FNDC5 and tissue-specific markers such as BDNF in brain, myostatin in muscle, and collagen I (COL-1) in the bone of 4-month-old young mice [ 32 ]. Interestingly, increased expression of FNDC5, improved tissue structural organization and increased BDNF expression were detected after exposure to a WBV protocol with shorter vibration exposure times and longer recovery times.…”
Section: Molecular Mediators Involved In Wbv Effectsmentioning
confidence: 88%
See 2 more Smart Citations
“…As physical exercise leads to an induction of FNDC5 in the hippocampus, the PGC1a/FNDC5/BDNF pathway has been proposed as playing a role in the neuroplastic effects of physical exercise [ 10 , 11 ]. Animal-based studies have also shown that three months of a whole-body vibration program might lead to the modulation of FNDC5 expression and BDNF in the brain [ 12 ]. Irisin is a cleaved version of FNDC5 and has been suggested as a potential mediator of the beneficial effects of exercise on human metabolism [ 13 ].…”
Section: Introductionmentioning
confidence: 99%